1979
DOI: 10.1002/cne.901860205
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular marking with Lucifer Yellow CH and horseradish peroxidase of cells electrophysiologically characterized as glia in the cerebral cortex of the cat

Abstract: Intracellular microelectrodes filled with either Lucifer Yellow CH, a highly florescent dye, or horseradish peroxidase (HRP) were used to electrophysiologically characterize and mark cells in the cerebral cortex of cat. Fifty-eight cells, characterized electrophysiologically as glia, were marked with Lucifer Yellow CH. All were identified as protoplasmic astrocytes, and included cells in the glia limitans of the molecular layer. An additional 54 cells, similarly characterized as glia, were labeled with HRP. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…These cells (n = 3) (Fig. 6, upper left) had the features of protoplasmic astro cytes as noted in previous studies (Takato and Goldring, 1979;Chesler and Kraig, 1987). Second, HRP was similarly injected (n = 14) into living as trocytes, but animals were then killed by cardiac arrest, and perfusion-fixation was delayed for 20-40 min to allow ischemic-morphologic changes to occur.…”
Section: Horseradish Peroxidase Stainingmentioning
confidence: 66%
“…These cells (n = 3) (Fig. 6, upper left) had the features of protoplasmic astro cytes as noted in previous studies (Takato and Goldring, 1979;Chesler and Kraig, 1987). Second, HRP was similarly injected (n = 14) into living as trocytes, but animals were then killed by cardiac arrest, and perfusion-fixation was delayed for 20-40 min to allow ischemic-morphologic changes to occur.…”
Section: Horseradish Peroxidase Stainingmentioning
confidence: 66%
“…However, the morphologies of neurons and glia have been extensively described (Fairen et al, 1977;Jones, 1975;Lund, 1973;Lund and Boothe, 1975;Peters and Jones, 1984a;Peters and Jones, 1984b;Takato and Goldring, 1979). These studies have established criteria that allow for discrimination between several cell types, based on their unique morphologies (e.g.…”
Section: Species Differences In the Distribution Of Dj-1 Protein In Hmentioning
confidence: 99%
“…The average long and short diameters of the soma were 5.9 and 3 9 ,tm, respectively (twenty-four cells), although these values were possibly over-estimated owing to the fluorescent halo. These structural features of the inexcitable cell generally conform to those of astrocytes (Dennis & Gerschenfeld, 1969;Kelly & van Essen, 1974;Takato & Goldring, 1979;Gutnick, Connors & Ransom, 1981 Dennis & Gerschenfeld, 1969), in vivo (38 mV, Ransom & Goldring, 1973a) and in culture (52 mV, Kettenmann, Sonnhof & Schachner, 1983;51 mV, Walz, Wuttke & Hertz, 1984). [K+o (mM) The input conductance of inexcitable cells during the slow potential was measured by passing hyperpolarizing current pulses of constant intensity (Fig.…”
Section: Morphology Of Inexcitable Cellsmentioning
confidence: 99%
“…They have demonstrated that the glial cell membrane behaves like T. TAKAHASHI AND H. TSURUHARA a K+ electrode and that a transient extracellular K+ accumulation caused by a nerve impulse produces a slow depolarizing potential in glial cells. Slow depolarizing potentials have also been observed in mammalian glia in vivo after tetanic nerve stimulation (Karahashi & Goldring, 1966;Somjen, 1970;Ransom & Goldring, 1973b;Lothman & Somjen, 1975;Takato & Goldring, 1979) or during drug-induced seizures (Sugaya, Goldring & O'Leary, 1964;Futamachi & Pedley, 1976). However, in the mammalian central nervous system in vivo, detailed studies of glial cells have been limited by the difficulties in attaining stable intracellular recordings and in controlling the extracellular ionic environment.…”
Section: Introductionmentioning
confidence: 99%